Greenhouse Gas Emissions an Index of Global Warming is not Associated with Ischemic Heart Disease Mortality - Singh, Ishmeet; Rabkin, Simon W (Cardiology and Cardiovascular Medicine, 2021)
Objective: The objective of this study was to examine the relationship between greenhouse gas (GHG) emissions and ischemic heart disease (IHD) and for comparison chronic lower respiratory tract disease (RESP) mortality, between different countries. Methods: The United Nations Framework Conven-tion on Climate Change (UNFCC) GHG inventory database for 2015 (37 countries) and 2016 (12 countries) was related to World Health Organization (WHO) age-standardized death rates per 100,000 for IHD and RESP diseases. The next approach was to focus on one country with a similar health care system, GHG for each province of Canada from 2013-2018 was related to age-standardized IHD mortality. Results: In the 2015 database, there was no significant correlation (r=0.046, p=0.785) between GHG and IHD mortality and similarly after excluding the 3 countries in the 90th percentile for GHG. In contrast, there was a suggestion of a relationship between GHG and RESP mortality (r=0.306, p=0.069). Evaluating countries with GHG values that were not in the upper 90th percentile showed a significant (r=0.380, p=0.03) relationship between GHG and RESP mortality. Focusing on one country with a similar health care system, GHG for each province of Canada from 2013-2018 was related to age-standardized IHD mortality. There was no increase in IHD mortality in regions with high compared to low GHG. Conclusion: These data suggest that greenhouse gas (GHG) emissions, an index of global warming is not associated with ischemic heart disease mortality while an association with chronic lower respiratory tract disease (RESP) mortality is possible.